Modelling methods for policy analysis in Miombo woodlands (Center for International Forestry Research, 2001)
The miombo woodlands of eastern, central and southern Africa are some of the most extensive dry forests in Africa. They supply a myriad of products and services for local populations, governments and the private sector - the main stakeholders. Planning the management and use of the woodlands to meet the needs of the many and diverse stakeholders who often have conflicting interests in the woodlands continues to be a great challenge to national governments and other interested parties. This paper presents two modelling approaches, a systems dynamics model and a goal programming model, that have potential for use in planning woodland use and in analysing the implications of various policies on people and the woodlands.